Theodicy of Jean-Jacques Rousseau - Tugnoli, Claudio (European Scientific Journal, ESJ, 2016)
Throughout all of Rousseauâ€™s works there is tension between argumentation and feeling, speculation and intuition, reason and conscience. Reason binds men when they think correctly, but divides them and opposes one to the other when they place it at the service of self-interest, of ambition and of the will to prevail. Conversely, the universality of conscience is immediate and transparent: it transmits the truth of the existence of God, of the freedom of men, of the distinction between good and evil, as well as of the universal principles that are at the roots of human action and of the virtues honoured by all human societies, despite the differences of particular legislations. Mankind possesses an innate and intuitive conscience of the fundamental principles by which its conduct must be inspired. Were we to consider human actions only according to the criterion of physical need, of causality and of movement, vices and virtues would disappear and terms like morality and honesty would have no meaning. But each one of us perceives from within that this is not the case. We feel that moral good and evil are more real than anything else, without any need whatsoever to prove it. To obey the conscience one has of good and of evil without human mediation means to reject the dogmatic formalism of religions as well as the vanity of philosophical disputes. Every human being, however, is inserted into a national community. What should the stateâ€™s attitude be vis-Ã -vis religion? Rousseau indicates two paths. The first consists in establishing a purely civil religion that admits only those dogmas that are truly useful to society. Rousseau highlights the contradiction of a Christian religion that, although it is the religion of peace par excellence, fuels continuing bloody clashes among men due to a dogmatic theology that is totally alien to the essence of the Gospel and extremely hazardous for the life of the State. The second path consists in allowing Christianity to retain its authentic spirit, its freedom from any material constraint, without any obligations other than those of individual conscience. The Christian religion has such a pure and noble moral that it cannot but benefit the State, as long as one does not expect to make it part of the constitution.